The relationship between organizational entrepreneurship and performance: evidence from Turkish smes - Akkaya, Nida Platin (My University, 2014)
ÖRGÜTSEL GİRİŞİMCİLİK VE PERFORMANS ARASINDAKİ İLİŞKİ:TÜRK KOBİ’LERİNDEN BULGULAR İstihdam ve bölgesel kalkınmayı sağlayarak ülke ekonomisinin gelişmesini ve güçlenmesini sağlayan KOBİ’ler bir ülkenin ekonomik gelişimi için hayati öneme sahiptirler. Bu araştırmanın amacı küçük işletmelerin büyümesini etkileyen faktörleri ve bu faktörler arasındaki ilişkileri bulmaktır. Bu faktörleri ve aralarındaki ilişkileri bulmak için bir model oluşturulmuştur. Bu model temel olarak büyümeyi etkileyen strateji ve bu stratejiyi etkileyen bağdaştırıcı faktörler üzerine kurulmuştur. Bu modele uygun olarak geliştirilen ölçüm aleti : şirket ve şirket sahibi ile ilgili rket stratejileri, girişimcilik faaliyetleri ve firmanın son 3 yıllık dönemdeki satış ve ihracat artışlarını kapsamaktadır. Tüm ölçeklerin soruları tek bir ankette birleştirilmiş ve toplam 72 soru olarak genellikle Ankara ve Bursa’da üretim yapan 163 KOBİ’ye uygulanmıştır. Sonuç girişimcilik yönelimine ait stratejilerin KOBİ’lerin satış ve ihracat performanslarını olumlu etkilediğini göstermektedir.Ayrıca her koşulda proaktif olmak durumunda olan KOBİ’ler özellikler ihracat söz konusu olduğunda proaktif ve yaratıcı olmaktan daha çok risk alan olmak zorundadırlar. Bu sonuçların gelecekteki çalışmalara ve KOBİ’lerin gelişimlerine yol göstermesi beklenmektedir. THE RELATIONSHIP BETWEEN ORGANIZATIONAL ENTREPRENEURSHIP AND PERFORMANCE: EVIDENCE FROM TURKISH SMEs Small and medium sized entreprises that are vital for a nation’s economy, contribute to development and welfare of economies by providing employment and regional development. This research aims to find the factors linked to Entrepreneurial orientation and corporate entrepreneurship that effect export and sales growth performance of SMEs.Thereby a model was developed to reveal the relationship between these factors. The questionnaire had parts such as general information about firm and owner/ manager, entrepreneurial orientation, corporate entrepreneurship and growth in sales revenue and exportation rate over the most recent 3 year period of the SMEs. The measurements have been gathered together in 72 item in survey and applied to 163 SMEs manufacturing generally in Ankara and Bursa, Turkey. The result showed that entrepreneurial orientation is positively and significantly related with SMEs’ sales growth and exportation performances. SMEs have to be proactive in any circumstances and especially exporter SMEs need to be more risk taking than proactive and least innovative. Also organizational boundaries has greater effect on performance than other dimensions of corporate entrepreneurship. The results are expected to be a guide for progress of SMEs in further studies.
Keywords: Girişimcilik; Küçük işletmeler; Örgütsel etkinlik